2019
DOI: 10.1186/s13567-019-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the prion protein gene (PRNP) sequence of wild deer in Great Britain and mainland Europe

Abstract: Susceptibility to prion diseases is largely determined by the sequence of the prion protein gene ( PRNP ), which encodes the prion protein (PrP). The recent emergence of chronic wasting disease (CWD) in Europe has highlighted the need to investigate PRNP gene diversity in European deer species, to better predict their susceptibility to CWD. Here we report a large genetic survey of six British deer species, including red ( Cervus elaphus ), si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…All animals were homozygous for glutamine (Q) at codon 95, glycine (G) at codon 96, methionine (M) at codon 132 and serine (S) at codon 225. These findings are consistent with PRNP sequences reported in Chinese [15], Japanese [16] and Korean sika deer [17], as well as a recent study involving European sika deer [18].…”
Section: Prnp Sequence Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…All animals were homozygous for glutamine (Q) at codon 95, glycine (G) at codon 96, methionine (M) at codon 132 and serine (S) at codon 225. These findings are consistent with PRNP sequences reported in Chinese [15], Japanese [16] and Korean sika deer [17], as well as a recent study involving European sika deer [18].…”
Section: Prnp Sequence Analysissupporting
confidence: 92%
“…The PRNP sequence was identical in all six sika deer in our study and had been previously identified in studies of Asian [15][16][17] and European sika deer [18]. Many of the alleles present in our sika deer have been associated with CWD susceptibility in other cervid species (95Q, 96G, 132M, 225S) [6].…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, Prnp polymorphisms can modulate susceptibility to CWD (Angers et al., 2014; Green et al., 2008; Hannaoui, Amidian, et al, 2017; Hannaoui, Schatzl, et al, 2017; Johnson et al., 2011). Previous studies reported a Prnp polymorphism resulting in a substitution from serine to asparagine at codon 138 (S138N) unique to fallow deer ( Dama dama ) and reindeer/caribou (Hamir et al., 2011; Mitchell et al., 2012; Moore et al., 2016; Rhyan et al., 2011; Robinson et al., 2019). This polymorphism has been associated with lower susceptibility to CWD in both species under experimental conditions, depending on the route of prion infection (Mitchell et al., 2012; Moore et al., 2016; Rhyan et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other deer species showed less variation, with roe and fallow deer having identical PRNP gene sequences in all the animals sampled. Based on comparison with PRNP sequences of NA cervids affected by CWD and limited experimental challenge data, the authors conclude that a high proportion of wild deer in Great Britain may be susceptible to CWD (Robinson et al., ). A similar conclusion was reached by a previous study of 715 genotyped cervids (red deer, roe deer and chamois) from the UK and Italy (Peletto et al., ).…”
Section: Assessmentmentioning
confidence: 99%